The Housing and Planning Act 2016: rewarding the aspiration of homeownership? - Bevan, Chris; Laurie, Emma (Wiley, 2017)
In May 2016 the Housing and Planning Act 2016 became law, the first purely Conservative government intervention on housing in England since the 1990s. This article examines the Act's key provisions pertaining to social housing and the government's stated aim of increasing rates of homeownership. The Act, through the Starter Homes Scheme, extension of the right to buy to housing association tenants and changes to security of tenure in the social sector, has been heralded as a ‘landmark’ piece of legislation. This article scrutinises these policy measures and assesses their effectiveness and likely impact. It is contended that the Act exposes the government's promotion of homeownership above all other housing tenures. The article further explores the deep moralisation at the heart of the homeownership narrative and the intensification in the residualisation of social housing in England which, it is argued, is the inevitable consequence of the reforms.